The Effect Of Puberty Education On Knowledge And Attitudes Related To Puberty Changes - Dina Qoyimatul; Friska Realita (Universitas Prima Indonesia, 2026)
Puberty is an important phase in adolescent development characterized by physical, psychological and social changes. Lack of understanding about pubertal changes can trigger anxiety and risky behavior. Puberty education is a strategic step in equipping adolescents with accurate information about reproductive health and body changes. This study aims to analyze the effect of puberty education on improving adolescents' knowledge and attitudes through the literature review method from various international and national studies in 2021-2025. The results of the analysis show that technology-based, interactive, and empowerment-based educational approaches are able to increase understanding and shape positive attitudes of adolescents towards puberty. In addition, family support and adaptation to adolescents' special needs also play an important role in the success of education. Innovations in learning methods, such as the use of mobile applications and Health Belief Model-based approaches, proved effective in improving pubertal health behaviors. These findings emphasize the importance of developing more inclusive and evidence-based puberty education policies to support adolescent well-being.